The Importance of Preoperative Evaluation to Predict the Outcome of Percutaneous Nephrostomy - Ronald J. Datu; Eko Arianto; Ari Astram; Christof Toreh (Universitas Sam Ratulangi, 2024)
Abstract: Percutaneous nephrostomy (PCN) is an invasive procedure equal to a grade 4 penetrating kidney trauma. It should be carefully considered whether has a greater benefit or risk. There are currently no parameters or scores to predict the outcome of nephrostomy in our center. This study aimed to conduct a review to find out whether there were parameters or scores that could be used to predict the outcome of nephrostomy. This research used relevant studies obtained from Clinical Key, PubMed, Semantic Scholar, Dimensions, and Science Direct published in the last 10 years and written in English. Studies on children and transplant cases were excluded. Studies that met the PICO criteria were selected. The results showed that of the 141 articles collected, and filtered with inclusion criteria, exclusion criteria, and PICO criteria, finally the remaining were three studies selected. The studies discussed about classification, SFU grading system, and complication of nephrostomy; significant variables affecting recoverability of renal function; patients’ characteristics and outcomes of double J ureteral stenting (DJS) and PCN; and 12-month-post-operative creatinine level change. Most patients who failed DJS had increased creatinine level. However, one of the indications for a nephrostomy was stenting failure. In conclusion, predictor factors that can affect the renal recovery after nephrostomy include kidney shape and size, pre-nephrostomy creatinine levels, urine output, state of infection, and degree of hydronephrosis. However, the evidence is still not enough. Further research is needed on the predictor factors for renal recovery after nephrostomy. Keywords: percutaneous nephrostomy; hydronephrosis; kidney function; predictors